(untitled) (Journal of the College of Basic Education, 2025)
Public administration performs the function of administrative control, to maintain public order with its various elements within society and the state, and thus protects the rights and freedoms of individuals from any attack on them. In order to achieve this, the public administration enjoys broad powers, but these powers are not absolute because absolute power corrupts absolutely, as the public administration must, in normal circumstances, exercise administrative control powers within the scope of the principle of legality, and it is subject to judicial control over its powers, but in circumstances Exceptionalism: The powers of administrative control bodies expand greatly, as the theory of exceptional circumstances allows them to take measures and carry out actions that were not considered legitimate under the normal rules of legality, in order to preserve public order and ensure the safety of the state, and this theory is A constitutionally organized theory, with clear texts , This is because the ordinary rules of legality do not allow administrative control bodies to carry out their tasks in maintaining public order, and do not provide them with the legal means to ensure that they carry out their tasks. However, this theory does not lead to the administration being freed from judicial oversight of its actions. This research comes to shed light on the function of administrative control, and the limits of the powers of administrative control bodies in normal and exceptional circumstances, so that these bodies do not exceed the limits set for them and infringe on the rights and freedoms of individuals.